Research on short process hot forming technology of a medium manganese steel. Issue 1 (1st December 2022) - Hou, Z R; Min, J Y; Wang, J F; Lu, Q; Zhang, X; Lin, J P
Abstract : Carbon neutrality and carbon peaking are one of the key tasks of our country in the future. As a major carbon producer, the steel industry played an important role in achieving energy conservation. The feasibility and benefits of rapidly heating (over 100 °C/s) has been proven to be effective for producing press hardening steel, which can also shorten the hot forming process. In this work, we studied the application of short hot forming process in a medium manganese steel. Results shown that the new process can greatly reduce the austenitizing time while ensuring the strength of the materials. In addition, the short-term heating of the material in a non-equilibrium state exacerbated the uneven distribution of alloying elements. Thus, the content of retained austenite in the final microstructure doubled (increased from 8.7% to 18.5%) through the new process, thereby further improving the toughness of the material. The microstructure evolution and mechanical properties of the material under the short process hot forming process was analysed, together with the feasibility of the new process in the future industrialization.